Contributions of natural climate variability on the trends of seasonal precipitation extremes over China. (14th April 2021) - Cao, Fuqiang; Gao, Tao; Dan, Li; Zhao, Fengxia; Gong, Xiang; Zhang, Xinyu; Long, Xiaoyu; Zhan, Junjie
Abstract: The increased trends of extreme precipitation events over China have been partially attributed to global warming, while it is unclear how the natural climate variability affect these variations in extreme rainfall trends. Here we examine the contributions of large‐scale modes climate variability from the Pacific Ocean, which are represented by El Niño‐Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO), on the trends of seasonal extreme events across China. Results show that the effects of climate variability modes on precipitation extremes exhibit evidently spatiotemporal characteristics at the seasonal scale. A significant positive trend is found over southeastern and northwestern China in four seasons, and substantial increases in two types of extreme events are also seen over northwestern China in spring and winter. Most of the seasonal trends of extreme precipitation events can be explained by the trends of the principal components. El Niño (La Niña) and PDO–like sea surface temperature (SST) anomalies over the Pacific have a close linkage with the variations in precipitation extremes. By modulating the large‐scale atmospheric circulations, these Pacific SST anomalies associated with climatic oscillations, such as ENSO and PDO, provide the conducive conditions responsible for the occurrences of seasonal precipitation extremes across China. The seasonal trends of extreme events can be largely explained by the variability of the ENSO and PDO episodes, with a relatively larger modulation of PDO as compared to ENSO. These researches have important implications for improving seasonal flood disaster predictability and climate model performances. Abstract : Most of the seasonal trends of extreme precipitation events can be explained by the trends of the principal components. El Niño (La Niña) and Pacific Decadal Oscillation (PDO)–like SST anomalies over the Pacific have a close linkage with the variations in extreme precipitation events. By modulating the large‐scale atmospheric circulations, these Pacific SST anomalies associated with climatic oscillations, such as El Niño‐Southern Oscillation (ENSO) and PDO, provide the suitable conditions that are conducive to the occurrences of extreme events over China. The seasonal trends of precipitation extremes can be partially explained by the interannual and interdecadal variability of the ENSO and PDO episodes, respectively, with a relatively larger modulation of PDO.